Comparison of turnout in Italian parliamentary elections: a two-stage affinity propagation approach - Daniela Ichim; Marianna Mantuano (Journal of Maps)
This paper presents a methodology for temporal contextual analysis of electoral outcomes in the presence of redistricting. Affinity propagation is used to aggregate electoral districts, thus deriving spatial units comparable over electoral waves. The methodology is based on travel-to-work flows and socio-economic aggregated data. Comparability of clusters enables analyses of electoral trends. A map of electoral turnout variation in Italian parliamentary elections held in 2018 and 2022 illustrates the proposed approach.